Senescence and the Aging Immune System as Major Drivers of Chronic Kidney Disease - Schroth, Johannes; Thiemermann, Christoph; Henson, Siân M. (Frontiers in Cell and Developmental Biology, 2020)
Chronic kidney disease (CKD) presents an ever-growing disease burden for the worlds ageing population. It is characterised by numerous changes to the kidney, including a decrease in renal mass, renal fibrosis and a diminished glomerular filtration rate. The premature ageing phenotype observed in CKD is associated with cellular senescence, particularly of renal tubular epithelial cells, which contributes to chronic inflammation through the production of a pro-inflammatory senescence associated secretory phenotype. When coupled with changes in immune system composition and progressive immune dysfunction, the accumulation of senescent kidney cells acts as a driver for the progression of CKD. The targeting of senescent cells may well represent an attractive therapeutic avenue for the treatment of CKD. We propose the targeting of senescent cells either by direct inhibition of pro-survival pathways (senolytics) or through the inhibition of their proinflammatory secretory profile (senomorphics) together with immunomodulation to enhance immune system surveillance of senescent cells could be of benefit to patients with CKD.